Chapter Recycling of Polymeric Composite Materials - Sabău, Emilia (InTechOpen, 2018)
This chapter treats studies about the methods and technologies used to recycle the polymeric composite materials and develop new recipes using waste of polymer composite materials resulted from recycling. Composite materials obtained from recycling are presented, with a complete recovery of waste glass fibers. Also, the mechanical properties for new structures of polymeric composite materials, containing additional materials were presented. These were obtained from the recycling of composite waste. A morphology analysis of fracture area of composites samples was done. At present, the polymeric composite materials present a great scientific and technical interest, which justify both the development of research in this field, and the expansion of production of such materials. The author treats aspects regarding a current problem due to the large number of polymeric composite materials waste, and reduced of environmental impact. This field is representing one of the top viable research directions.